Konstruk dan Model Pembiayaan Musyarakah Mutanaqishah Di Bank Syariah - Rokhim, Abdul (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2014)
Syariâah banks today are growing rapidly, both in Indonesia and internationally. Syariâah banks provide a new alternative for users of banking services to customers enjoy products with a profit-sharing system, a wide range of products covenants contained therein, including in the case of a partnership contract, in which the Islamic bank as a business corporation berproduk Musharaka mutanaqishah describe the activities and institutions that produce banking services for financing partnership assets decreased according to customer needs, but there is still debate about the implications for both the practical and the academic world.